A imprensa estudantil liceísta maranhense na Primeira República (1907-1930) - Furtado, Luciana Nathalia Morais (2016)
It presents the speeches of lyceist students in the Maranhenses student periodicals from 1910 to 1930 in order to identify and analyze the appropriation tactics of the students expressed in the published news as well as to understand the school dynamics and representations about pedagogic activities such as methods, Examinations, forms of entrance, curriculum, evaluations that characterized the daily life of secondary education in the first republican decades and the students' demands on the problems and the precise demands for this modality of education. Therefore, this study is based on the bibliographical research based on the principles of Cultural History in authors such as Castellanos (2007, 2012); Castro, 2006; Chartier, 1999; Nóvoa, 2002; Barros, 2013, among others, allowing us to understand the History of Pedagogical Press, History of Maranhão Education, specifically Secondary Education and documentary research, in which we focus on the mapping and analysis of the vestiges expressed in the following newspapers: O Progresso (1907) ; O Brazil (1907); The Left-Handed (1912-1914); Excelsior (1914); The Student (1915); Lábaro (1921); Alma Nova (1929) and the Young Blood (1930). A study of the periodic educational press liceitas made it possible to understand the sociopolitical changes that sustained the production of the school media when exposing ideas that evidenced the republican period; The development of the country, the creation of schools and the implementation of innovative methods in secondary public education in Maranhão. It was contacted that the student writings constituted in a privileged channel for the exhibition and circulation of the knowledge and of denunciation on the lack of educational policies. In this way, we consider that the newspapers written by the students of the Liceu were configured as an important vehicle of identity and resistance between the ideal and the concrete lived by the students of this institution in the First Republic.